(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
To communicate clear in English, the pronunciation and intonation plays crucial role. However, nowadays all around the world including Asia, English pronunciation is still abandoned in ESL classrooms. One of the apparent reason is lack of English pronunciation teaching strategies and techniques to teachers. This article outlines several strategies to improve pronunciation and intonation, supported by research and best practices in language instruction.